Nursing management of incontinence associated dermatitis complicated with fungal infection in a critically ill patient (1例危重症患者失禁性皮炎合并真菌感染的护理体会) - ZHANG Ning (张宁); ZHANG Chunyan (张春艳); YUE Yuzi (岳玉姿); LIU Huan (刘欢); TANG Ling (唐玲); HAN Jianping (韩建萍); SUN Lei (孙磊); LI Ying (李影); ZHOU Jie (周洁) (Association of Integrative Nursing, 2022)
This paper summarized the clinical treatment and nursing measures of incontinence associated dermatitis complicated with fungal infection in a critically ill patient. Targeted plan of catheter maintenance and skin care was made based on the assessment of patient conditions. The Traditional Chinese Medicine collapse stains method was used to relieve the pain and inflammation, and accelerate the wound healing. (本文总结 1 例危重症患者失禁性皮炎合并真菌感染的临床治疗及护理措施。根据患者个体情况, 制定针对性的管路护理和皮肤护理措施, 同时基于中医理论指导, 运用中药塌渍法缓解疼痛、促进炎症吸收, 加快皮肤创面愈合。)